Combination of apatinib and continuous nutritional support for a gastric cancer patient with brain metastasis prolongs survival. (18th May 2018) - Yang, Y.; Pei, X.; Yang, M.
Summary: What is known and objectives: Gastric cancer is the most common gastrointestinal malignant tumour in China, which rarely metastasizes into the central nervous system. However, brain metastasis leads to increased risk of death. Case summary: Here, we report a case of brain metastasis from gastric cancer, which was treated with apatinib and continual nutritional support, with a survival time of 2 years. What is new and conclusion: The combination of apatinib and continual nutritional support may be an option for the treatment of brain metastasis from gastric cancer. A prospective study should be performed to confirm this. Abstract : The combination of apatinib and continual nutritional support may be an option for the treatment of brain metastasis from gastric cancer. MRI revealed tumour size shrink after the treatment.